FAMILY RESILIENCE STRATEGIES IN THE DIGITAL ERA ACCORDING TO THE QUR'AN - mono, derys (el-Umdah, 2023)
Abstract: Digital progress is so rapid, it has a good impact on humans, so they can communicate between countries and continents, easy access to information and digitalization. However, there are negative impacts on human life, for example cyber crime, pornography, LGBT and others, which pose a threat to families in Indonesia. So in this study, attempts to explain the concept of family resilience in the Koran and how the strategy of family resilience from the perspective of QS Tahrim: 6. The conclusion of this study is that what is meant by family resilience is a form of protection, mitigation, or prevention and self-defense in the face of various threats and danger to the family as well. There are at least four strategies in family resilience in QS At-Tahrim verse 6 from the perspective of Tafsir Ibnu Katsir, religious education, improving the quality of communication between families, collective family protection based on maqashid sharia, state protection for families. Keywords: Strategy, Family Resilience, Digital Age.